Market based instruments, ecosystem services and development in Mission Beach, Far North Queensland. Background report 2, Urbanisation and the Cassowary: impacts and economics - Coggan, Anthea; Whitten, Stuart M., 1970-; Marine and Tropical Sciences Research Facility (Queensland); Reef and Rainforest Research Centre; CSIRO. Sustainable Ecosystems (Cairns, Qld : Reef and Rainforest Research Centre on behalf of the Australian Government's Marine and Tropical Sciences Research Facility, 2009)
This second background report gives a brief description of the cassowary along with some key habitat requirements. This is followed by an analysis of the human and urbanisation impacts on cassowaries in Mission Beach. The undersupply of cassowaries is discussed from an economic angle through an analysis of current markets and market failures. The conditions for government intervention, conclusions for this report and implications for the next report are discussed in the concluding section.
Title from PDF cover page (viewed on September 10, 2014)
"Supported by the Australian Government's Marine and Tropical Sciences Research Facility Project 4.9.6 Strategic Natural Resource Management and Land Use Planning, Task (c) Implementing Ecosystem Goods and Services."
"Report first completed June 2007. Published by RRRC March 2009." -- PDF title page verso.
Report to the Marine and Tropical Sciences Research Facility.
Includes bibliographical references (pages 21-22)
Mode of access: Available online (as at 10/09/2014) at: http://rrrc.org.au/publications/research_reports-html
Keywords: Ecosystem management -- Queensland -- Mission Beach; Ecosystem services -- Queensland -- Mission Beach; Cassowaries -- Queensland -- Mission Beach Region; Wildlife conservation -- Economic aspects -- Queensland -- Mission Beach Region; Mission Beach (Qld.) -- Environmental conditions